Analysis on the cause of eosinophilia in a neonatal intensive care unit - Jeoung Young Kim; Hyo Bin Im; Min Jung Sung; Sang Hee Son; Son Sang Seo (Korean Pediatric Society, 2010)
Purpose : Although eosinophilia is a common laboratory finding in many neonatal intensive care units (ICUs), its causative mechanisms remain obscure. We aimed to determine the causes of eosinophilia in the neonatal ICU environment. Methods : Serial eosinophil counts were determined weekly for 288 hospitalized, appropriately grown neonates. Infants were divided into four groups according to gestational age, and the incidence and etiologic factors of eosinophilia were retrospectively studied. Results : Absolute eosinophilia (>700/mm3) was documented in 18% (52/288) of neonates. Twenty-two infants (42.3%) exhibited mild eosinophilia (700-999 cells/mm3), 27 (51.9%) exhibited moderate eosinophilia (1,000–2,999 cells/mm3), and 3 (5.8%) exhibited severe eosinophilia (>3,000 cells/mm3). Of the 288 infants studied, 54 suffered sepsis. Thirty of these 54 infants (55.6%) showed eosinophilia, and 22 out of the remaining 234 infants (9%) without sepsis showed eosinophilia, indicating that eosinophilia was more prevalent in the sepsis group (P<0.05). All 5 infants suffering from bronchopulmonary dysplasia showed eosinophilia, and 47 out of the remaining 283 infants (16.7%) without bronchopulmonary dysplasia showed eosinophilia. Thus, eosinophilia was more prevalent in the bronchopulmonary dysplasia group (P<0.05). Furthermore, increased prevalence of eosinophilia was associated with respiratory distress syndrome, ventilator use, blood transfusion, and total parenteral nutrition (P<0.05). Conclusion : Our results suggest that eosinophilia is influenced by sepsis and bronchopulmonary dysplasia, although it can also occur idiopathically at birth. Moreover, the potential role of eosinophils in conditions such as wound healing and fibrosis in sepsis or chronic lung disease may be a cause of eosinophilia.